2003
DOI: 10.1007/978-1-4757-5129-1
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Studies on Volatility in International Stock Markets

Abstract: Aims and ScopeThe series will place particular focus on monographs, surveys, edited volumes, conference proceedings and handbooks on:• Nonlinear dynamic phenomena in economics and finance, including equilibrium, disequilibrium, optimizing and adaptive evolutionary points of view; nonlinear and complex dynamics in microeconomics, finance, macroeconomics and applied fields of economics.• Econometric and statistical methods for analysis of nonlinear processes in economics and finance, including computational meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 103 publications
(269 reference statements)
0
3
0
1
Order By: Relevance
“…Moreover, it is well known that the time series of realized measures are also persistent. For example, Andersen et al (2003), Andersen et al (2009) and Hol (2003) emphasized the evidence of long memory in the time series of realized measures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is well known that the time series of realized measures are also persistent. For example, Andersen et al (2003), Andersen et al (2009) and Hol (2003) emphasized the evidence of long memory in the time series of realized measures.…”
Section: Introductionmentioning
confidence: 99%
“…Rejeb and Boughrara (2015) have investigated financial integration in emerging market economies and its impact on volatility transmission and contagion and have concluded that financial liberalization contributes significantly in amplifying the international transmission of volatility and the risk of contagion. Hol (2003) has provided Stochastic Volatility (SV) models as an applied alternative to the Generalised Autoregressive Conditional Heteroskedasticity (GARCH) models. Dutta et al (2017) have investigated the effect of oil volatility shocks on global emerging market stock returns and have concluded that the OVX index shocks generate a high impact on emerging market equity returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the mathematics presented here are more related to some financial tools than to classical bibliometric studies, and this is the main novelty of our work. Although we have not followed any special financial model, our arguments can be understood in economic terms: the interested reader can find more information about such models for example in Hol (2013) and the references therein.…”
Section: Introductionmentioning
confidence: 99%